2002
DOI: 10.1051/0004-6361:20021535
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the properties of the central engine in microlensed QSOs

Abstract: Abstract. We study a recently observed gravitational microlensing peak in the V-band light curve of Q2237+0305A using a relatively simple physical model, but one that is highly consistent with the data (the best-fit reduced χ 2 is very close to 1). The source quasar is assumed to be a Newtonian geometrically-thin and optically-thick accretion disk. The disk has an arbitrary orientation, and both blackbody and greybody emission spectra are considered. When the electron-photon scattering plays a role, the greybo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…By applying this method to the V light curve of the lensed component A in the Einstein Cross, Lee et al (2005) have found that a torus source model may easily account for the observed light curve of component A, especially for the double peak present in the GLITP data. So far, Shalyapin et al (2002) and Goicoechea et al (2003) have also investigated this observed HAE in terms of a Newtonian geometrically thin and optically thick accretion disk. They used the same GLITP data, but the results derived from the PSF fitting photometry, not those obtained by the ISIS image subtraction technique presented in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…By applying this method to the V light curve of the lensed component A in the Einstein Cross, Lee et al (2005) have found that a torus source model may easily account for the observed light curve of component A, especially for the double peak present in the GLITP data. So far, Shalyapin et al (2002) and Goicoechea et al (2003) have also investigated this observed HAE in terms of a Newtonian geometrically thin and optically thick accretion disk. They used the same GLITP data, but the results derived from the PSF fitting photometry, not those obtained by the ISIS image subtraction technique presented in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…2. It is clear that whereas components A and C show a small but significant variability (see Shalyapin et al 2002 andGoicoechea et al 2003, for the interpretation of the variation in the component A as the peak of a high-magnification event), images B and D remain relative flat, showing no signs of strong microlensing during the monitoring period. As the expected time delays between the images are short (≤1 day, see Schneider et al 1988;Wambsganss & Paczyński 1994), intrinsic fluctuations would show up in all 4 images almost simultaneously.…”
Section: Monitoring Observations Of Q2237+0305mentioning
confidence: 99%
“…Nevertheless, it is convenient to have a representation of K cr in the form of expansion in powers of small parameter. Such an expansion can be fulfilled correctly after substitution of K cr into integral (36). On this way, starting from form (18), it is easy to show that to define K cr correctly, one must replace the term Θ(y 2 )(y 2 ) for any test function f (y).…”
Section: From a Point Source To Extendedmentioning
confidence: 99%
“…On the other hand, a number of authors [4,16,[33][34][35][36][37][38][39] discussed delicate questions concerning determination a fine quasar structure from HAE. For example, the authors of [36] wrote that the GLITP data [28] on Q2237+0305 admit only accretion disc models (see also [4,39]). Obviously, the presence of an accretion disk in a central region of quasar is beyond any doubts, as well as the fact that the real appearance of the quasar core can be quite different from our simplified models.…”
Section: Preliminary Commentsmentioning
confidence: 99%